Orofacial injuries and use of protective wear among field hockey players of Coorg District, Karnataka, India – A KAP Study - Jaseela Praveena; Hemant Battur; Nusrath Fareed; Sanjeev Khanagar; Manohar Bhat (Indian Journal of Dental Research, 2018)
Introduction: Traumatic orofacial injuries are frequent among hockey players, often causing aesthetic, functional, psychological, and economic problems. This study was conducted to assess the prevalence and distribution of orofacial injuries and to assess the knowledge, attitude and practices toward the use of protective wear as perceived among hockey players of Coorg district. Methods: A cross-sectional descriptive study was conducted among 281 field hockey players of Coorg district, Karnataka, India. Data were collected using a specially designed self-administered, pretested questionnaire containing a set of 19 statements. Chi-square test was performed to assess statistical significance among the variables studied. P value <0.05 was considered statistically significant. Results: The mean age of the study sample was 32.7 ± 4.3 years, and majority of them were semi-professional hockey players (46.6%) with an experience of 5–10 years (41.3%) of playing hockey and having at least a graduate qualification (65.5%). A total of 79% of the players reported to have been injured at least once in the past 1 year, of which orofacial injuries accounted for 33.8% of the injuries. Majority of the players had a fair Knowledge, Attitude and Practice (KAP) score toward the use of protective wear (63.7%). Although 37.7% of the players had good knowledge, it translated to a favorable attitude among 24.1% of the players and favorable practice among 11.7% players. Professional hockey players had a positive association with KAP scores (P < 0.00), whereas experience was found to be negatively associated with KAP scores (P < 0.03). Conclusion: The majority of players had moderate knowledge about the importance of protective wear in preventing orofacial injuries, but their attitude and practices toward the same were relatively poor.